The generative capacity of sticker systems with weights - Yee, Sian Gang; Wan, Heng Fong; Sarmin, Nor Haniza; Turaev, Sherzod (2014)
DNA computing involves computation models which use the recombination behavior of DNA molecules as the computation rules. This idea was successfully applied by Adleman in his biological experiment in order to show the solvability of the Hamiltonian path problem for larger instances. In 1998, a DNA based computation model, called sticker systems, which is an abstraction of the computations using the recombination behavior as in Adleman's experiment was proposed. In 2013, a new variant of sticker system using weights was introduced, namely the weighted sticker system. In this paper, the generative capacity for several variants of bounded delay and nonrestrictive weighted sticker systems are investigated. The relation between families of languages generated by several variants of weighted sticker systems and weighted grammars are also presented.